2013
DOI: 10.1111/pedi.12071
|View full text |Cite
|
Sign up to set email alerts
|

Night glucose control with MD-Logic artificial pancreas in home setting: a single blind, randomized crossover trial-interim analysis

Abstract: Original ArticleNight glucose control with MD-Logic artificial pancreas in home setting: a single blind, randomized crossover trial -interim analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 29 publications
(33 reference statements)
1
76
0
2
Order By: Relevance
“…Results of these studies demonstrate the safety and efficacy of the MD-Logic system, which achieved significantly less hypoglycemia and tighter overnight glucose control than the standard treatment (i.e., continuous subcutaneous insulin infusion or sensor-augmented pump [SAP] therapy) (2,(12)(13)(14).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Results of these studies demonstrate the safety and efficacy of the MD-Logic system, which achieved significantly less hypoglycemia and tighter overnight glucose control than the standard treatment (i.e., continuous subcutaneous insulin infusion or sensor-augmented pump [SAP] therapy) (2,(12)(13)(14).…”
mentioning
confidence: 92%
“…Over the past 5 years, a number of studies have been carried out to assess the safety and efficacy of the MD-Logic system for overnight glucose control in children, adolescents, and adults in various settings (2,(12)(13)(14). Results of these studies demonstrate the safety and efficacy of the MD-Logic system, which achieved significantly less hypoglycemia and tighter overnight glucose control than the standard treatment (i.e., continuous subcutaneous insulin infusion or sensor-augmented pump [SAP] therapy) (2,(12)(13)(14).…”
mentioning
confidence: 99%
“…Subsequent studies confirmed these findings in outpatient setting, 47 at diabetes camps for children, 48 and at patients' homes. 49 The superior glucose control achieved by these trials suggests that when CGM information is processed appropriately by advanced algorithms, the clinical outcomes are better, even than those achieved by state-of-the art sensoraugmented insulin pump therapy. 50,51 Thus, CGM data contain valuable information reaching beyond the episodic BG determinations provided by SMBG.…”
Section: Utility Of Cgm Informationmentioning
confidence: 99%
“…Comparisons between closed-loop and open-loop insulin delivery systems were performed using the paired nonparametric Wilcoxon signed rank test. The power of the nonparametric tests for the primary endpoint was based on the results of power simulations (MATLAB 2013b, MathWorks) based on previous studies [11,23,24]. We calculated that enrolment of 20 participants would provide a power of 90% for detecting a 30% reduction in the proportion of time spent with blood glucose levels below 3.3 mmol/l, at a 0.05 two-sided significance level, assuming a 30% dropout.…”
Section: Devices and Assaysmentioning
confidence: 99%